Pembagian Harta Warisan Disaat Pewaris Masih Hidup Telaah Pasal 187 Ayat (1) Kompilasi Hukum Islam (KHI) - Naskur Naskur (IAIN Manado, 2017)
The inheritance process between heirs and inheritor is in the event of death to the inheritors, either in essence, rule or decision of Islam. Death to the inheritor is the principal requirement and distinguishing of process of transfer of wealth in form of inheritance with the transfer of wealth in form of inheritance. However, the provision, the complication of Islamic law provides another alternative in the distribution of a person’s wealth that deviates from provision of Islamic inheritance law. Moreover, the objective and benefit of examining this alternative is to know the justified boundaries in the deviation of the process of dividing person’s wealth in the form of inheritance and to detect the Islamic law toward this deviation. The deviation of the main provision of the distribution of a person’s is expressed to be inheritance is limited to the distribution of the wealth which if it has been done at the time of the death of the heir, will occur bickering and disagreement between family which will cause harm. The divergence limit can be justified by Islamic law provision not harm the right of ownership of the inheritor’s legacy. Keywords: inheritance of alive heir, the limit